Professional learning for secondary teachers of English learners in an urban school district: examining systems of support. Issue 2 (26th October 2021) - Weddle, Hayley; Yoshisato, Mariko; Hopkins, Megan
Abstract : Purpose: Although schools across the United States are becoming increasingly linguistically and culturally diverse, many teachers remain underprepared to work with students classified as English learners (ELs), especially at the secondary level. Acknowledging the importance of developing systems of support for teachers of ELs, this paper examines the district- and school-level factors shaping secondary teachers' access to EL-focused professional learning in one large urban school district. Design/methodology/approach: To examine teachers' access to EL-focused professional learning, the authors draw on 49 in-depth interviews with district leaders and staff from nine secondary schools. Data analysis was guided by a structure, culture and agency theoretical framework. Findings: Findings revealed that decreased structural support, in terms of both fiscal and human resources, constrained teachers' access to EL-related professional learning. Further, the district culture was characterized by limited understanding of ELs' backgrounds and assets. While some school leaders exercised agency to bolster EL-focused professional learning for teachers, such supports were rare. Practical implications: Findings help to contextualize secondary teachers' feelings of unpreparedness to serve ELs, illuminating several factors that district and school leaders should attend to in order to bolster the development of professional capital for teachers of ELs at the secondary level. Originality/value: While prior research outlines the importance of designing systems of support for EL-focused professional learning, this study highlights specific structural and cultural factors shaping such systems.